Web-Based Student Grade Management Information System - Indri Anugrah Ramadhani; Sahiruddin Sahiruddin; Muhamad Ali Kasri; Soleha Alhamid (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
Digital transformation is pushing schools to adopt efficient academic information systems, but many schools in 3T areas including SMK Muhammadiyah Aimas still manage grades manually, making them prone to input errors, data duplication, and slow academic recap and reporting processes. This situation shows how important it is to find a systematic way to make value management more accurate, efficient, and open. This research aims to develop and evaluate a web-based system for managing value, designed to meet the needs of vocational schools in a limited context. Using a Research and Development (R&D) approach, the developed system integrates master data management, daily values, midterm exams, final exams, attendance, and automatic final grade calculation. The test results show that all features function according to specifications, while expert validation places the software aspect in the